PETROGRAPHIC ANALYSIS OF TRACE FOSSIL DESMOGRAPTON FUCHS, 1895 FROM THE MIOCENE OF NORTHERN APENNINES (ITALY): A METHODOLOGY TO DETECT HYPICHNIAL FEATURES AND IMPLICATIONS ON THE GRAPHOGLYPTID ETHOLOGY - ALESSIO CHECCONI; PAOLO MONACO (Rivista Italiana di Paleontologia e Stratigrafia, 2013)
The trace fossil Desmograpton Fuchs, 1895, as many other graphoglyptids, has been considered to be a typical pre-turbidite, three-dimensional burrow system formed in mud and preserved as a casting at the sole of turbidites. This classic interpretation was mostly based on hypichnial preservation, due to the lack of direct evidence (e.g. modern seafloor pictures) for pre-depositional or post-depositional origin. Due to the accidental series of processes invoked to explain the perfect hypichnial preservation of this delicate trace fossil, several doubts and questions have been raised. To try to clarify the sedimentary processed that lead this trace fossil to be preserved, 26 thin sections of Desmograpton dertonensis Sacco, 1888 and Desmograpton ichthyforme Macsotay, 1967 have been performed at sand/clay interface of thin-bedded sandstone turbidites in the Miocene marl deposits of Verghereto, Northern Apennines (Italy). Petrographic analysis of textures and grains of the burrow-filling sediments points out that most of the grains of burrows differ from those of overlying sand, being either more or less sorted and differ in composition and locally also in grain size. Burrows are occasionally characterised by an upper rim, more or less thick, enriched in glauconite, phosphates, pyrite or quartz. Axial cuts of the strings show that rim was involved in diagenetic compaction, squeezing and fluid migration modifying the original shape of the trace fossil. In pre-depositional conditions the oblique-oriented filling is the only explication to preserve the upper rim of original mud, while compaction produced asymmetry in hypichnial tunnels. This petrographic approach, performed for the first time on this graphoglyptid genus, also elucidates the complex interaction of several taphonomic processes that led to the preservation of Desmograpton. The application of a similar petrographic approach to other graphoglyptids could help to better understand their origin, ethology and their preservation processes.